(untitled) (Al-Qamar, 2020)
This paper studies the role of Akbar Ilahabādī and Mawlānā Zafar ʻAlī Khān in social reforms. It maintains that restructuring of society has been the first attempt of the reformers of the Ummah. Writers, historians, preachers and poets are considered to be the most sensitive people in the society, so their purpose in life is the welfare of the people and through their writings they inspire people in such a way that people live in the society in a good manner. Akbar Ilahabādī and Mawlānā Zafar ʻAlī Khān have also played their role for the betterment of both Muslim and non-Muslim society without any discrimination. Both of these poets have taken up the cause of reforming the society with their humorous and serious style and method and have drawn the attention of the people towards the problems found in the society. Akbar Ilahabādī has tried to inculcate in the people of society love for the friends of God, awareness of knowledge, adoption of humility and submission, avoidance of turning away from the teachings of the Quran and the Gospels, modesty and harmony between Muslims and Hindus, while Mawlānā Zafar ʻAlī Khān has showed the love for the family of the Prophet, highlighted the greatness of man, the greatness of Muslims of past. He pointed out issues like attention to humanity, love of humanity, hard work, liberation from slavery and harmony between Muslims and Hindus.